POLA KOMUNIKASI INTERAKSI ANTARA PENGUSAHA SOUVENIR PAGAR ALAM DENGAN TURIS LOKAL - Meri Ekri Nensi; Ainur Ropik; Gita Astrid (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Politik Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study discusses / examines the pattern of communication interactions between Pagar Alam souvenir entrepreneurs and local tourists. by raising the problem of how the pattern of communication interaction between Pagar Alam souvenir entrepreneurs and local tourists. The purpose of this study was to determine the pattern of communication interaction between Pagar Alam souvenir entrepreneurs and local tourists. The methodology used is descriptive qualitative research with the presentation of data analyzed in depth using secondary data, primary data, observation, interviews, documentation, using the symbolic interaction theory of Herbert Blummer used in this study. The results showed that the communication carried out by Pagar Alam souvenir entrepreneurs with local tourists used verbal communication and nonverbal communication, but not too much use of non-verbal communication, the more important role here is verbal communication itself. Verbal communication carried out by store employees is question and answer communication, where when the buyer asks the employee will answer and will ask more questions to get what information the buyer wants so that the employee can give the best to the buyer. Keywords: Communication, Souvenir, Tourist